Fostering Environmental Knowledge and Literacy with Natural Products Experiment Activity Worksheets - Murbangun Nuswowati; Harjito Kusmanto; Harjono Harjono; Nuryanto Nuryanto; Ainu Ilmiatuz Zahro; Aisyah Mohamad Sharif (Jurnal Tadris Kimiya, 2024)
This research aims to improve student environmental knowledge and literacy with natural products experiment activity worksheets. The methods used in this research are pre-experimental. The subjects of this research are 15 students from an Islamic high school. The research results show that natural products experiment activity worksheets effectively improve students' learning outcomes. The research results indicate that the pre-test results obtained an average score of 50.8, indicating that students needed help understanding the material before using natural products' experiment activity worksheets. Post-test results showed an average score of 80.5, indicating that students experienced increased learning outcome scores. The average normalized gain score is 0.59, indicating a medium increase in chemistry learning outcomes. The self-assessment questionnaire on environmental literacy, conducted after using the integrated natural products experiment activity worksheets, showed that knowledge had an average score of 4.33 and was rated as excellent, behavior had an average score of 4.31 and was rated as good, and attitude had an average score of 4.37 and was also rated as good. Overall, students' environmental literacy was rated as outstanding, with an average score of 86.74%.